Contribution of the Role of the School Committee to the Implementation of School-Based Management in Elementary School - Sapitri, Riris; Kurniawan, Pendi; Eka Cipta, Samudra (Samsara Institute Publisher, 2025)
This article explores the role of school committees in supporting educational programs at the elementary level through a literature review. Achieving educational goals requires active involvement from the community and stakeholders, especially parents as primary users of educational services. Their participation plays a crucial role in enhancing the quality of education and fostering a collaborative partnership with schools. Therefore, school committees should function as strategic partners in implementing school programs. The findings indicate that a strong partnership between schools and school committees contributes significantly to improving educational quality. Committees are actively involved in coordinating with schools in planning both academic and non-academic activities, including social and community programs. Their roles encompass providing input, support, supervision, and acting as a communication bridge between schools and parents. When the functions and partnerships of school committees are well-established, schools can effectively implement various programs aimed at improving educational outcomes. This collaboration helps schools achieve their vision and mission while also increasing parental satisfaction. Ultimately, the active role of school committees becomes a vital element in strengthening the quality of education at the elementary level.